The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/00224278221120781
|View full text |Cite
|
Sign up to set email alerts
|

Who Believes that the Police Use Excessive Force? Centering Racism in Research on Perceptions of the Police

Abstract: Objectives Police use of excessive—even fatal—force is a significant social issue, one at the symbolic heart of the Black Lives Matter civil rights movement. However, a substantial number of Americans—disproportionately White—tend to minimize the prevalence of this issue. We seek to explain differences in these views. Methods We look at whether experiences with the police, politics, and three measures of racial attitudes explain differences in views of the prevalence of police use of excessive force, and we sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 153 publications
0
2
0
Order By: Relevance
“…For example, in September 2020, 91% of Black Americans acknowledged that Black Americans are treated less fairly than White Americans when interacting with police, while 58% of White Americans acknowledged this disparity (Horowitz et al, 2020). And, compared to Black and Latinx Americans, White Americans have higher anti-Black attitudes, which explains why they are less likely to believe that police use excessive force-before, during, and after the murder of George Floyd (Drakulich et al, 2022). Therefore, the large presence of White protestors at the subsequent protests for justice was not only historically unique but also unrepresentative of many White Americans' reported acknowledgment of racism in policing.…”
Section: Perceptions Of Police Brutality and Protests For Justicementioning
confidence: 99%
See 1 more Smart Citation
“…For example, in September 2020, 91% of Black Americans acknowledged that Black Americans are treated less fairly than White Americans when interacting with police, while 58% of White Americans acknowledged this disparity (Horowitz et al, 2020). And, compared to Black and Latinx Americans, White Americans have higher anti-Black attitudes, which explains why they are less likely to believe that police use excessive force-before, during, and after the murder of George Floyd (Drakulich et al, 2022). Therefore, the large presence of White protestors at the subsequent protests for justice was not only historically unique but also unrepresentative of many White Americans' reported acknowledgment of racism in policing.…”
Section: Perceptions Of Police Brutality and Protests For Justicementioning
confidence: 99%
“…Second, we examined how alarmed (e.g., emotionally jarred) participants were by the murder of George Floyd and the presence of White protestors. Previous research demonstrates the negative impact of police brutality on Black Americans’ perceptions (e.g., Bor et al, 2018) as well as the lack of White American acknowledgment of police brutality due to anti-Black attitudes (e.g., Drakulich et al, 2022). Thus, we expected a main effect of race on reports of how alarmed participants were such that Black (relative to White) Americans would be more alarmed by both the murder of George Floyd and the significant level of White people at subsequent protests for justice.…”
Section: The Racialized Impact Of Police Brutalitymentioning
confidence: 99%
“…For example, recent research has found that racial resentmenta view that downplays the relevance of historical discrimination and blames racial inequality on Black peopleis a significant factor in shaping perceptions of police among white Americans. Drakulich et al (2022a) found that racial resentment plays an important role in explaining racial stratification in perceptions of the prevalence of excessive force in policing.…”
Section: Chapter 7: Conclusionmentioning
confidence: 99%